Does magnetic resonance represent the gold-standard of imaging for the follow-up of arthritis? - M.A. Cimmino (PAGEPress Publications, 2011)
Several studies suggest that MRI is between 2 and 10 times superior to conventional radiology in the visualization of erosions. This higher sensibility is dependent on the specific joint assessed, the precocity of the disease, and the timing of follow-up. In addition, MRI can depict bone oedema, which is an early and reversible bone lesion, and evaluate the degree of inflammation of the synovial membrane. A single examination could therefore evaluate disease activity and damage. The sensitivity to change of articular MRI is good, as demonstrated by a number of follow-up studies. In view of these advantages, it may be surprising that MRI has not yet become the gold standard of imaging of the arthritic joint. The three main reasons are low availability of high field machines, examination's costs, and lack of standardization of the technique. Low field extremity-dedicated MRI machines are probably the answer to the first two concerns. They have been shown to obtain reliable results for the clinician, and to be relatively cheap and patientfriendly, allowing repeated follow-up examinations. As far as standardization is concerned, there are many studies addressing the problem, with OMERACT as the driving force. MRI is likely to represent the future of the follow up of arthritis for the evaluation of its pace of progression and the effect of treatment. The advent of new and potent biologic therapies has incremented the need for more sensible imaging methods and will probably drive their diffusion in clinical practice.